Advances in 3D printing combined with tissue engineering for nerve regeneration and repair - Weifang Liao; Yuying Shi; Zuguang Li; Xiaoping Yin (Journal of Nanobiotechnology, 2025)
Abstract The repair of nerve damage has long posed a challenge owing to limited self-repair capacity and the highly differentiated nature of nerves. While new therapeutic and pharmacologic interventions have emerged in neurology, their regenerative efficacy remains limited. Tissue engineering offers a promising avenue for overcoming the limitations of conventional treatments and increasing the outcomes of regenerative repair. By implanting scaffolds into damaged nerve tissue sites, the repair and functional reconstruction of nerve injuries can be significantly facilitated. The integration of three-dimensional (3D) printing technology introduces a novel approach for accurate simulation and scalably fabricating neural tissue structures. Tissue-engineered scaffolds developed through 3D printing technology are expected to be a viable therapeutic option for nerve injuries, with broad applicability and continued development. This review systematically examines recent advances in 3D printing and tissue engineering for nerve regeneration and repair. It details the basic principles and construction strategies of neural tissue engineering and explores the crucial role of 3D printing technology. Additionally, it elucidates specific applications and technical challenges associated with this integrated approach, thereby providing valuable insights into innovative strategies and pragmatic implementation within this field. Graphical Abstract